The effects of whole body vibration on postural control: The frequency of stimulation - Simsek, D.; Kirkaya, I.; Ruhi Soylu, A.; Ugurlu, O.; Cerrah, A. O.; Ertan, H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study investigated the efficacy of high and low-frequency acute whole-body vibration (WBV) on postural control ability. WBV stimulus were applied the following determinants: (1) type (vertical) (2) frequency (30 and 40 Hz), (3) stance position (static squat position), (4) amplitude (4mm mm), (5) knee flexion angle (120°) and time (60s).Motion of the point of application of the vertical component [medio-lateral (ML) and anterio-posterior (AP)] of the ground reaction force (center of pressure, COP). The study results showed that static WBV stimuli given at low and high frequencies and 4 mm amplitude resulted in a different postural adaptation (p<0.05). The somatosensory stimulation more rapidly adapted to the vibration at 40 Hz-4 mm.